Magic foods for better blood sugar - Wait, Marianne, 1967- (Pleasantville, N.Y. : Reader's Digest Association, 2007)
A breakthrough solution to our hidden health crisis. Learn how to live longer, supercharge your energy, lose weight, and stop cravings.
Includes index.
Keywords: Nutrition -- Popular works; Food -- Composition -- Popular works; Blood sugar -- Popular works